If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 328 = 8(5 + -6x) 328 = (5 * 8 + -6x * 8) 328 = (40 + -48x) Solving 328 = 40 + -48x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '48x' to each side of the equation. 328 + 48x = 40 + -48x + 48x Combine like terms: -48x + 48x = 0 328 + 48x = 40 + 0 328 + 48x = 40 Add '-328' to each side of the equation. 328 + -328 + 48x = 40 + -328 Combine like terms: 328 + -328 = 0 0 + 48x = 40 + -328 48x = 40 + -328 Combine like terms: 40 + -328 = -288 48x = -288 Divide each side by '48'. x = -6 Simplifying x = -6
| (8m^−2n^6)(1/2^n−2) | | 2(1x-8)-3(1x+2)=-24 | | 20-(x+7)=7x-3 | | -7x+5=8x-25 | | -3(x+4)-11x= | | 6-7x=7x-10x-2 | | -240-8(4k-6)= | | (12k+3w)+(6k-4w)= | | 12-15/3-3 | | 5x+4y=10b-x | | 4(3t-2)+10=6(t-2)-(5t+3) | | 1/4(x-8)=2 | | 3b/5=-2 | | 20x+48=20x | | 12x^2y-8x^3y^2+11x^2y-4x^3y^2-9xy^2= | | 104+4x-8=-8+17x | | 3W-12W=81 | | 6.3=2x-4.6 | | 18+15=0 | | -12q=52 | | -14=-15x | | 3q-6+2=5q-2q-7 | | 2(2n+4)=7(7n+5)+7 | | -2(x-1)+3=19 | | 8+7x-6x=-4x+4x | | 6x+8x-66=110-8x | | 2+4+x=-14 | | -132/4= | | 10(g+5)-2(g+9)= | | 243x^3-243x^2-729x+729=0 | | 2y^2-y+3=0 | | (x-y)(x+y)1+2+3+4+5(2x+2xy)=0 |